2018
DOI: 10.26444/aaem/94675
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of <i>Toxoplasma gondii</i> infection in cats in southwestern Poland

Abstract: Objective. An assessment of the prevalence of Toxoplasma gondii infection in cats from southwestern Poland using serology, coproscopy and PCR methods. Materials and method. In total, 208 cats (139 females and 68 males), aged 0.5-12 years (mean=2.6) from 25 localities in southwestern Poland were examined by indirect immunofluorescence assay (IFAT) to estimate the T. gondii serological status. Faecal samples of 41 cats were examined for the presence of oocysts/DNA T. gondii by microscopy and Real-time/nested PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
13
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 33 publications
(40 reference statements)
7
13
3
Order By: Relevance
“…gondii seroprevalence studies in feline populations have been conducted over the last decade [ 5 ]. The result of the present survey shows that the infection rate in Cyprus (32.3 %) is consistent with the recently reported prevalences in most areas in Europe, even though in some countries, such as Poland, France, Estonia and Albania, percentages of over 60.0% have been recorded [ 29 , 30 , 31 , 32 , 33 ]. During the last decade, the highest percentage of seropositive animals (84.7%) was recorded in the island of Majorca, in feral cats [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…gondii seroprevalence studies in feline populations have been conducted over the last decade [ 5 ]. The result of the present survey shows that the infection rate in Cyprus (32.3 %) is consistent with the recently reported prevalences in most areas in Europe, even though in some countries, such as Poland, France, Estonia and Albania, percentages of over 60.0% have been recorded [ 29 , 30 , 31 , 32 , 33 ]. During the last decade, the highest percentage of seropositive animals (84.7%) was recorded in the island of Majorca, in feral cats [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the study of cat sera for the presence of antibodies against T. gondii, positive results were obtained in almost 75% of cases. This result is in agreement with earlier serological studies [40] and with the well-established view on the main role of the cat as a definitive host of T. gondii, excreting infective oocysts into soil and water [5]. In the presented study, a distinct increase of seroprevalence was found with cats' age in up to 100% in animals more than 10-years-old.…”
Section: Discussionsupporting
confidence: 93%
“…In Europe, several T. gondii seroprevalence studies in feline populations have been conducted over the last decade [5]. The result of the present survey shows that the infection rate in Cyprus (32.3 %) is consistent with the recently reported prevalences in most areas in Europe, even though in some countries, like Poland, France, Estonia and Albania, percentages of over 60% have been recorded [32][33][34][35][36]. During the last decade, the highest percentage of seropositive animals (84.7%) was recorded in the island of Majorca, in feral cats [37].…”
Section: Discussionsupporting
confidence: 85%